Transmission belt

The transmission belt with a rubber composition optimized for elastic modulus and load vibrations addresses the challenge of achieving high transmission capabilities and excellent speed change response, outperforming existing technologies by balancing high and low stress region moduli.

JP7661022B2Active Publication Date: 2025-04-14BANDO CHEM IND LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2020179939
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-27
Publication Date
2025-04-14
Estimated Expiration
2040-10-27

AI Technical Summary

Technical Problem

Existing transmission belts with V-sides formed from rubber compositions struggle to achieve high transmission capabilities and excellent speed change response.

Method used

A transmission belt with a power transmission portion on the V side formed from a specific rubber composition, which is characterized by its freshly stored elastic modulus of compression when subjected to specific load vibrations and temperatures, optimizing the balance between high transmission capacity and speed change response.

Benefits of technology

The described transmission belt achieves high transmission capabilities and excellent speed change response, effectively addressing the limitations of existing technologies by maintaining high modulus in high stress regions while keeping it relatively low in low stress regions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661022000003
    Figure 0007661022000003
  • Figure 0007661022000004
    Figure 0007661022000004
  • Figure 0007661022000005
    Figure 0007661022000005
Patent Text Reader

Abstract

To provide a transmission bolt which is high in transmission capability, and excellent in gear change responsiveness.SOLUTION: A transmission belt B is formed of a rubber composition at a power transmission part of a V-side face 11a. In the rubber composition, a storage Young's modulus E'L of compression when the load vibration of compression stress between 0.25 MPa and 0.5 MPa is imparted at a frequency of 10 Hz under a temperature of 100°C in a belt width direction is equal to or lower than 220 MPa, and the E'H of compression when the load vibration of compression stress between 1.0 MPa and 2.0 MPa is imparted at a frequency of 10 Hz under a temperature of 100°C is equal to or higher than 220 MPa.SELECTED DRAWING: Figure 1A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a power transmission belt. [Background technology]

[0002] Power transmission belts having a V-shaped side made of a rubber composition are known. For example, Patent Document 1 discloses a power transmission belt having a V-shaped side made of a rubber composition in which cellulose nanofibers and carbon black are dispersed in a rubber component. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent No. 6271823 Summary of the Invention [Problem to be solved by the invention]

[0004] An object of the present invention is to provide a power transmission belt having high power transmission capacity and excellent speed change response. [Means for solving the problem]

[0005] The present invention relates to a power transmission belt in which a power transmission portion on a V-side surface is formed of a rubber composition, and the rubber composition has a compressive storage modulus E' when a load vibration of a compressive stress between 0.25 MPa and 0.5 MPa is applied at a frequency of 10 Hz at a temperature of 100°C in the belt width direction. L but 214MPa The compression modulus of elasticity E' is less than or equal to 1.0 MPa, and the compression modulus of elasticity E' is less than or equal to 1.0 MPa when a compressive stress of 1.0 MPa to 2.0 MPa is applied at a frequency of 10 Hz at a temperature of 100°C. H but 231MPa That's all. Effect of the Invention

[0006] According to the present invention, the compression storage modulus E' of the rubber composition forming the power transmission part of the V side surfaceL but 214MPa The compression storage elastic modulus E' is less than or equal to H but 231MPa As a result of the above, it is possible to obtain high transmission capacity as well as excellent gear change response. [Brief description of the drawings]

[0007] [Figure 1A] FIG. 1 is a perspective view of a piece of a double-cogged V-belt according to an embodiment. [Figure 1B] 1 is a cross-sectional view taken along the belt width direction of a double-cogged V-belt according to an embodiment. [Figure 1C] 1 is a cross-sectional view taken along the belt length direction of a double-cogged V-belt according to an embodiment. [Diagram 2] FIG. 2 is a perspective view of a test piece for measuring the compression storage elastic modulus E'L, E'H. [Diagram 3] FIG. 2 is a front view showing the pulley layout of a belt running test machine for measuring power transmission capacity. [Figure 4] FIG. 2 is a front view showing the pulley layout of a belt running test machine for evaluating durability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The embodiments will be described in detail below.

[0009] 1A to 1C show a double cogged V-belt B (power transmission belt) according to an embodiment. The double cogged V-belt B according to the embodiment is a power transmission member used as a speed change belt in a speed change device of a two-wheeled vehicle, for example. The double cogged V-belt B according to the embodiment has, for example, a belt length of 700 mm or more and 1400 mm or less, a maximum belt width of 16 mm or more and 40 mm or less, and a maximum belt thickness of 8.0 mm or more and 18.0 mm or less.

[0010] The double-cogged V-belt B according to the embodiment includes an endless rubber belt body 11. The belt body 11 has a cross-sectional shape along the belt width direction that is formed by combining an isosceles trapezoid on the belt inner periphery side and a horizontally elongated rectangle on the belt outer periphery side in a layered manner. The angle between the V-shaped side surfaces 11a on both sides of the belt body 11 is, for example, 24° or more and 36° or less. The belt body 11 is composed of three layers: a compressed rubber layer 111 on the belt inner periphery side, an adhesive rubber layer 112 in the middle in the belt thickness direction, and an tensile rubber layer 113 on the belt outer periphery side. The V-shaped side surfaces 11a on both sides of the belt body 11 are composed of both sides of the compressed rubber layer 111 and the adhesive rubber layer 112, and a part of both sides of the tensile rubber layer 113 on the belt inner periphery side. The side surfaces of the compressed rubber layer 111 occupy the largest proportion of the V-shaped side surfaces 11a, and this constitutes the power transmission section.

[0011] The double cogged V-belt B according to the embodiment includes a covering cloth 12 provided to cover the surface of the compressed rubber layer 111 on the inner circumferential side of the belt. On the inner circumferential side of the compressed rubber layer 111, lower cog forming parts 111a having a sine curve-shaped cross section along the belt length direction are arranged at a constant pitch. The lower cog forming parts 111a are covered with the covering cloth 12 to form the lower cogs 13. The double cogged V-belt B according to the embodiment includes a core wire 14 embedded in the middle part of the adhesive rubber layer 112 in the belt thickness direction. The core wire 14 is provided to extend in the circumferential direction while forming a spiral having a pitch in the belt width direction. On the outer circumferential side of the tension rubber layer 113, upper cogs 15 having a rectangular cross section along the belt length direction are arranged at a constant pitch.

[0012] The compressed rubber layer 111 is formed of a rubber composition A. The rubber composition A forming the compressed rubber layer 111 is obtained by crosslinking an uncrosslinked rubber composition in which various rubber compounding agents are blended and kneaded with a rubber component, by heating and pressurizing the composition. The rubber composition A is provided so that the grain direction corresponds to the belt width direction and the anti-grain direction corresponds to the belt length direction.

[0013] Examples of the rubber component of the rubber composition A include chloroprene rubber (CR), ethylene-propylene copolymer (EPR), ethylene-propylene-diene terpolymer (EPDM), ethylene-octene copolymer, ethylene-butene copolymer, and other ethylene-α-olefin elastomers, chlorosulfonated polyethylene rubber (CSM), hydrogenated acrylonitrile rubber (H-NBR), etc. The rubber component is preferably one of these rubbers or a blend of two or more of these rubbers, and from the viewpoint of obtaining high power transmission capacity and excellent shift response, it is more preferable to include chloroprene rubber (CR), and even more preferable to include sulfur-modified chloroprene rubber (sulfur-modified CR).

[0014] From the viewpoint of obtaining high power transmission capacity and excellent shift response, the rubber composition A preferably contains cellulose-based fine fibers dispersed in the rubber component as a rubber compounding agent. The cellulose-based fine fibers are fiber materials derived from cellulose fine fibers composed of skeletal components of plant cell walls obtained by finely breaking down plant fibers. Examples of raw plant materials for the cellulose-based fine fibers include wood, bamboo, rice (rice straw), potato, sugarcane (bagasse), waterweed, seaweed, etc. Among these, wood is preferred.

[0015] The cellulose-based fine fibers include cellulose fine fibers themselves and hydrophobized cellulose fine fibers obtained by subjecting the cellulose fine fibers to a hydrophobization treatment. The cellulose-based fine fibers preferably include one or both of these.

[0016] Examples of the cellulose-based fine fibers include those with a high aspect ratio produced by mechanical defibration means and those with needle-like crystals produced by chemical defibration means. The cellulose-based fine fibers preferably contain one or both of these, and more preferably contain cellulose-based fine fibers produced by mechanical defibration means from the viewpoint of obtaining high power transmission capacity and excellent gear shift responsiveness.

[0017] The average fiber diameter of the cellulose-based fine fibers is, for example, 10 nm or more and 1000 nm or less. The average fiber length of the cellulose-based fine fibers is, for example, 0.1 μm or more and 1000 μm or less. From the viewpoint of obtaining high power transmission ability and excellent gear shift responsiveness, the content of the cellulose-based fine fibers in the rubber composition A is preferably 1 part by mass or more and 10 parts by mass or less, more preferably 1.5 parts by mass or more and 5 parts by mass or less, and even more preferably 2 parts by mass or more and 3 parts by mass or less, based on 100 parts by mass of the rubber component.

[0018] From the viewpoint of obtaining high power transmission capacity and excellent shift response, the rubber composition A preferably contains carbon black dispersed in the rubber component as a rubber compounding agent. Examples of carbon black include channel black; furnace black such as SAF, ISAF, N-339, HAF, N-351, MAF, FEF, SRF, GPF, ECF, and N-234; thermal black such as FT and MT; and acetylene black. The carbon black preferably contains one or more of these, and from the viewpoint of obtaining high power transmission capacity and excellent shift response, it is more preferable to contain carbon black having an arithmetic average particle size of 50 μm or less, and even more preferable to contain FEF.

[0019] In order to obtain high power transmission capacity and excellent gear shift responsiveness, the content of carbon black in rubber composition A is preferably 30 parts by mass or more and 70 parts by mass or less, more preferably 36 parts by mass or more and 59 parts by mass or less, and even more preferably 41 parts by mass or more and 49 parts by mass or less, per 100 parts by mass of the rubber component.

[0020] When the rubber composition A contains cellulose-based fine fibers and carbon black, the content of carbon black in the rubber composition A is preferably greater than the content of cellulose-based fine fibers from the viewpoint of obtaining high power transmission ability and excellent gear shift response. From the same viewpoint, the ratio of the content of carbon black to the content of cellulose-based fine fibers in the rubber composition A (carbon black content / cellulose-based fine fiber content) is preferably 10 or more and 30 or less, more preferably 15 or more and 23 or less, and even more preferably 17 or more and 19 or less.

[0021] From the viewpoint of obtaining high power transmission capacity and excellent gear shift response, the rubber composition A preferably contains, as a rubber compounding agent, short fibers dispersed in the rubber component so as to be oriented in the grain direction, that is, in the belt width direction. The short fibers are preferably subjected to an adhesion treatment such as an RFL treatment to impart adhesion to the compressed rubber layer 111 of the belt body 11.

[0022] Examples of the short fibers include para-aramid short fibers (polyparaphenylene terephthalamide short fibers, copolyparaphenylene-3,4'-oxydiphenylene terephthalamide short fibers), meta-aramid short fibers, nylon 66 short fibers, polyester short fibers, polyvinyl alcohol short fibers, heterocycle-containing aromatic short fibers, ultra-high molecular weight polyolefin short fibers, polyparaphenylene benzobisoxazole short fibers, polyarylate short fibers, cotton, glass short fibers, carbon short fibers, etc. The short fibers preferably contain one or more of these, and from the viewpoint of obtaining high transmission capacity and excellent shift response, it is preferable to contain para-aramid short fibers, and more preferably to contain copolyparaphenylene-3,4'-oxydiphenylene terephthalamide short fibers.

[0023] From the viewpoint of obtaining high power transmission capacity and excellent gear shift responsiveness, the fiber length of the short fibers is preferably 1 mm or more and 5 mm or less, more preferably 2 mm or more and 4 mm or less. From the same viewpoint, the fiber diameter of the short fibers is preferably 5 μm or more and 30 μm or less, more preferably 10 μm or more and 15 μm or less.

[0024] In order to obtain high transmission capacity and excellent gear shift responsiveness, the content of the short fibers in rubber composition A is preferably 20 parts by mass or more and 40 parts by mass or less, more preferably 23 parts by mass or more and 37 parts by mass or less, and even more preferably 25 parts by mass or more and 34 parts by mass or less, per 100 parts by mass of the rubber component.

[0025] When rubber composition A contains cellulose-based fine fibers and short fibers, the content of short fibers in rubber composition A is preferably greater than the content of cellulose-based fine fibers from the viewpoint of obtaining high power transmission capacity and excellent gear shift responsiveness. From the same viewpoint, the ratio of the content of short fibers to the content of cellulose-based fine fibers in rubber composition A (content of short fibers / content of cellulose-based fine fibers) is preferably 7 or more and 17 or less, more preferably 9 or more and 15 or less, and even more preferably 11 or more and 13 or less.

[0026] When the rubber composition A contains carbon black and short fibers, the content of the short fibers in the rubber composition A is preferably less than the content of carbon black from the viewpoint of obtaining high power transmission ability and excellent shift response. From the same viewpoint, the ratio of the content of the short fibers to the content of the carbon black in the rubber composition A (content of short fibers / content of carbon black) is preferably 0.35 to 1.0, more preferably 0.45 to 0.79, and even more preferably 0.55 to 0.75. From the same viewpoint, the sum of the contents of the carbon black and the short fibers in the rubber composition A is preferably 50 to 90 parts by mass, more preferably 60 to 79 parts by mass, and even more preferably 65 to 74 parts by mass, per 100 parts by mass of the rubber component.

[0027] The rubber composition A may contain other rubber compounding agents such as a crosslinking agent, an antioxidant, a plasticizer, a processing aid, a co-crosslinking agent, a vulcanization accelerator, and a vulcanization acceleration aid.

[0028] From the viewpoint of obtaining high power transmission capacity and excellent gear shift response, the tensile strength in the grain direction of rubber composition A at a temperature of 25° C. is preferably 40 MPa or more, more preferably 46 MPa or more, and even more preferably 48 MPa or more. From the same viewpoint, the elongation at break in the anti-grain direction of rubber composition A at a temperature of 25° C. is preferably 50% or more, more preferably 64% or more, and even more preferably 66% or more. These tensile strengths and elongations at break are measured based on JIS K6251:2010.

[0029] The rubber composition A has a compression storage modulus E' of 100°C in the grain direction, i.e., in the belt width direction, when a compressive stress load oscillation between 0.25 MPa and 0.5 MPa is applied at a frequency of 10 Hz. L is 220 MPa or less, and from the viewpoint of obtaining high transmission capacity and excellent gear change responsiveness, it is preferably 165 MPa or more and 213 MPa or less, more preferably 192 MPa or more and 210 MPa or less, and even more preferably 196 MPa or more and 207 MPa or less.

[0030] The rubber composition A has a compression storage modulus E' of 1.0 MPa to 2.0 MPa when a compressive stress of 1.0 MPa to 2.0 MPa is applied at a frequency of 10 Hz at a temperature of 100°C in the grain direction, i.e., in the belt width direction. H is 220 MPa or more, and from the viewpoint of obtaining high power transmission capacity and excellent gear shift responsiveness, it is preferably 230 MPa or more and 260 MPa or less, more preferably 232 MPa or more and 260 MPa or less, and even more preferably 244 MPa or more and 256 MPa or less.

[0031] Compressive storage modulus of elasticity E' H Compression of the storage elastic modulus E' L Ratio to (E' H / E' L From the viewpoint of obtaining high transmission capacity and excellent gear shift response, the ratio is preferably 1.1 or more and 1.28 or less, more preferably 1.13 or more and 1.27 or less, and even more preferably 1.22 or more and 1.25 or less.

[0032] Here, the storage modulus of elasticity of these compressions E' L ,E' H The measurement is performed by cutting out a belt piece 20 from the double cogged V-belt B according to the embodiment so as to have a thickness of 10 mm in the belt width direction as shown in FIG. 2, setting the test piece 20 in a viscoelasticity measuring device, and compressing the portion corresponding to the compressed rubber layer 111 in the belt width direction.

[0033] The adhesive rubber layer 112 and the tension rubber layer 113 are also formed of a rubber composition obtained by crosslinking an uncrosslinked rubber composition, which is made by mixing a rubber component with various rubber compounding agents and then kneading the uncrosslinked rubber composition, by heating and pressurizing, in the same manner as the compressed rubber layer 111. The rubber composition forming the adhesive rubber layer 112 and / or the tension rubber layer 113 may be the same as the rubber composition A forming the compressed rubber layer 111.

[0034] The covering fabric 12 is made of, for example, a woven fabric, knitted fabric, nonwoven fabric, etc., formed of threads such as cotton, polyamide fiber, polyester fiber, aramid fiber, etc. It is preferable that the covering fabric 12 is subjected to an adhesive treatment such as an RFL treatment in order to impart adhesiveness to the compressed rubber layer 111.

[0035] The core wire 14 is composed of twisted yarns of polyester fiber, polyethylene naphthalate fiber, aramid fiber, vinylon fiber, etc. It is preferable that the core wire 14 is subjected to an adhesive treatment such as an RFL treatment in order to impart adhesiveness to the adhesive rubber layer 112.

[0036] According to the double-cogged V-belt B according to the embodiment having the above-described configuration, the compression storage modulus E' of the rubber composition A forming the compression rubber layer 111 constituting the power transmission portion of the V side surface 11a is L is 220MPa or less, and the compression storage elastic modulus E' H By having a modulus of elasticity of 220 MPa or more, it is possible to obtain high power transmission capacity and excellent gear shift response. This is presumably because, although the power transmission capacity is increased by increasing the modulus of elasticity in the high stress region of the power transmission part, the modulus of elasticity is relatively low in the low stress region, which suppresses the deterioration of gear shift response. Such an effect is particularly effective in applications where belt B is subjected to high torque and high load, such as the case of a transmission for a large two-wheeled vehicle in which the minimum winding diameter of belt B around the pulley is 70 mm or more.

[0037] The double cogged V-belt B according to the embodiment can be manufactured by a known method that has been conventionally and generally performed.

[0038] In the above embodiment, the double-cogged V-belt B is used, but the present invention is not limited thereto, and may be a single-cogged V-belt in which lower cogs are provided only on the inner circumferential side of the belt, or a raw-edge V-belt in which no cogs are provided. Furthermore, the present invention may be a V-ribbed belt in which the power transmission portion on the V side is formed of a rubber composition.

[0039] In the above embodiment, the belt is configured to include a covering cloth 12 covering the inner surface of the belt, but this is not particularly limited to this. In addition to the covering cloth 12 covering the inner surface of the belt, or instead of the covering cloth 12 covering the inner surface of the belt, a covering cloth may be provided to cover the outer surface of the belt, or a configuration may not include a covering cloth covering the inner and outer surfaces of the belt. EXAMPLES

[0040] (Double Cogged V-belt) The double cogged V-belts were produced in the following Examples 1 to 6 and Comparative Examples 1 to 4. The configuration of the rubber composition forming each of the compressed rubber layers is also shown in Table 1.

[0041] <Example 1> A composite material (manufactured by Tosoh Corporation) in which 2.5 parts by mass of cellulose-based fine fibers (average fiber diameter: 1000 nm or less) were blended with 100 parts by mass of sulfur-modified CR was added to an internal mixer and kneaded, and then 40 parts by mass of carbon black (Seat SO (FEF) manufactured by Tokai Carbon Co., Ltd., arithmetic mean particle size: 43 μm), 5 parts by mass of magnesium oxide, 2.3 parts by mass of antioxidants (Nocrac AD-F: 2 parts by mass, Nocrac 8C-N: 0.3 parts by mass, manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), 5 parts by mass of plasticizer (DOS manufactured by Taoka Chemical Industry Co., Ltd.), 1 part by mass of processing aid (stearic acid), 5 parts by mass of co-crosslinking agent (Valnoc PM (m-phenylenedimaleimide) manufactured by Ouchi Shinko Chemical Industry Co., Ltd.), and 10 parts by mass of zinc powder (UF powder) were added to the internal mixer and kneaded. The mixture was then charged into an internal mixer and kneaded, and 5 parts by mass of zinc oxide and 30 parts by mass of RFL-treated para-aramid short fibers (Technora (copolyparaphenylene-3,4'-oxydiphenylene terephthalamide short fibers) manufactured by Teijin Limited, fiber length: 3 mm, fiber diameter: 12 μm) were charged and kneaded relative to 100 parts by mass of sulfur-modified CR to prepare an uncrosslinked rubber composition.

[0042] Then, this uncrosslinked rubber composition was arranged so that the grain direction corresponded to the belt width direction and the anti-grain direction corresponded to the belt length direction, and a compressed rubber layer was formed from the crosslinked rubber composition to produce a double cogged V-belt having the same configuration as in the above embodiment, and this was designated Example 1.

[0043] The adhesive rubber layer and tension rubber layer were formed from a rubber composition whose rubber component was sulfur-modified CR. The covering fabric was made of polyester fiber woven fabric that had been RFL-treated and rubber paste-treated. The core wire was made of twisted para-aramid fiber that had been RFL-treated and rubber paste-treated. The belt size was 1200 mm in length, 33 mm in maximum width, and 16.0 mm in maximum thickness.

[0044] <Example 2> A double-cogged V-belt having the same configuration as in Example 1 was produced, except that the contents of carbon black and para-aramid short fibers in the rubber composition forming the compressed rubber layer were 45 parts by mass and 25 parts by mass, respectively, per 100 parts by mass of sulfur-modified CR, and this was designated Example 2.

[0045] <Example 3> A double-cogged V-belt having the same configuration as that of Example 1 was produced, except that the contents of carbon black and para-aramid short fibers in the rubber composition forming the compressed rubber layer were 35 parts by mass and 35 parts by mass, respectively, per 100 parts by mass of sulfur-modified CR, and this was designated Example 3.

[0046] <Example 4> A double-cogged V-belt having the same configuration as in Example 1 was produced, except that the contents of carbon black and para-aramid short fibers in the rubber composition forming the compressed rubber layer were 50 parts by mass and 25 parts by mass, respectively, per 100 parts by mass of sulfur-modified CR, and this was designated Example 4.

[0047] <Example 5> A double-cogged V-belt having the same configuration as in Example 1 was produced, except that the contents of carbon black and para-aramid short fibers in the rubber composition forming the compressed rubber layer were 60 parts by mass and 25 parts by mass, respectively, per 100 parts by mass of sulfur-modified CR, and this was designated Example 5.

[0048] <Example 6> A double-cogged V-belt having the same configuration as that of Example 1 was produced, except that the contents of carbon black and para-aramid short fibers in the rubber composition forming the compressed rubber layer were 50 parts by mass and 30 parts by mass, respectively, per 100 parts by mass of sulfur-modified CR. This was designated Example 6.

[0049] <Comparative Example 1> A double-cogged V-belt having the same structure as in Example 4 was produced as Comparative Example 1, except that the rubber composition forming the compressed rubber layer did not contain cellulose-based fine fibers.

[0050] <Comparative Example 2> A double-cogged V-belt having the same configuration as in Example 1 was produced, except that the rubber composition forming the compressed rubber layer did not contain cellulose-based fine fibers, and the contents of carbon black and para-aramid short fibers were 35 parts by mass and 25 parts by mass, respectively, per 100 parts by mass of sulfur-modified CR. This was designated Comparative Example 2.

[0051] <Comparative Example 3> A double-cogged V-belt having the same configuration as in Example 1 was produced, except that the rubber composition forming the compressed rubber layer did not contain cellulose-based fine fibers, and the contents of carbon black and para-aramid short fibers were 45 parts by mass and 35 parts by mass, respectively, per 100 parts by mass of sulfur-modified CR. This was designated Comparative Example 3.

[0052] <Comparative Example 4> A double-cogged V-belt having the same configuration as in Example 1 was produced, except that the contents of carbon black and para-aramid short fibers in the rubber composition forming the compressed rubber layer were 45 parts by mass and 30 parts by mass, respectively, per 100 parts by mass of sulfur-modified CR, and this was designated Comparative Example 4.

[0053] [Table 1]

[0054] (Test Method) <Tensile properties of rubber materials> A crosslinked rubber sheet was prepared by press molding the uncrosslinked rubber sheet of the uncrosslinked rubber composition used to form the compression rubber layer of each of the double cogged V-belts of Examples 1 to 6 and Comparative Examples 1 to 4. Then, a No. 3 dumbbell test piece was punched out from the uncrosslinked rubber sheet, and the tensile strength in the grain direction and the elongation at break in the anti-grain direction at a temperature of 25°C were measured based on JIS K6251:2010.

[0055] <Compression characteristics of rubber materials> For each of the double cogged V-belts of Examples 1 to 6 and Comparative Examples 1 to 4, a rubber strip was cut out from the uncrosslinked rubber sheet of the uncrosslinked rubber composition used to form the compression rubber layer so that the grain direction in which the para-aramid short fibers were oriented was the width direction, and the rubber strip was rolled up and press molded to prepare a disk-shaped compression test specimen having a diameter of 29 mm and a thickness of 12.5 mm in which the para-aramid short fibers were oriented in the thickness direction. The compression test specimen was then set in a viscoelasticity measuring device so that the thickness direction was the compression direction, and a load vibration of a compression stress between 0.25 MPa and 0.5 MPa was applied at a temperature of 100°C at a frequency of 10 Hz, and the compression vertical elastic modulus E' was measured. L In addition, the compression storage modulus E' was measured when a compressive stress between 1.0 MPa and 2.0 MPa was applied at a frequency of 10 Hz at a temperature of 100°C. H was measured.

[0056] <Belt compression characteristics> For each of the double cogged V-belts of Examples 1 to 6 and Comparative Examples 1 to 4, a belt piece having a length of 50 mm was cut out so that the thickness in the belt width direction was 10 mm, as shown in Fig. 2. The belt piece was then set as a test piece 20 in a viscoelasticity measuring device so that the belt width direction was the compression direction, and a load vibration of a compressive stress between 0.25 MPa and 0.5 MPa was applied at a temperature of 100°C at a frequency of 10 Hz to the portion corresponding to the compressed rubber layer, and the compression vertical elastic modulus E' at that time was measured. L In addition, the compression storage modulus E' was measured when a compressive stress between 1.0 MPa and 2.0 MPa was applied at a frequency of 10 Hz at a temperature of 100°C. H was measured.

[0057] <Transmission capacity> 3 shows a belt running tester 30 for measuring power transmission capacity. This belt running tester 30 for measuring power transmission capacity includes a drive pulley 31 having a pulley diameter of 111 mm, and a driven pulley 32 provided beside the drive pulley 31 and also having a pulley diameter of 111 mm.

[0058] For each of the double cogged V-belts B of Examples 1 to 6 and Comparative Examples 1 to 4, the belt was wound around the driving pulley 31 and the driven pulley 32, and in a state where an axial load DW (dead weight) was applied so as to generate belt tension, the driving pulley 31 was rotated at 1800 rpm to run the belt, and the rotation load of the driven pulley 32 was increased to calculate the transmission torque when the apparent slip ratio became 2.5%. This belt running test was then performed by gradually increasing the axial load DW on the driven pulley 32 from 1470 N to a maximum of 2744 N, and the maximum transmission torque obtained among them was determined. The transmission capacity was expressed as a relative value when the maximum transmission torque of Comparative Example 1 was set to 100.

[0059] <Gear shift response> The double cog V-belts of Examples 1 to 6 and Comparative Examples 1 to 4 were wound around the driving pulley and driven pulley of the transmission of a two-wheeled vehicle for testing, and the belt was run between the driving pulley and driven pulley by operating the engine. With the engine running at full throttle, the belt was wound around the driving pulley with an internal centrifugal roller exerting a pressing force to narrow the gap between the grooves of the driving pulley as the engine speed increased, and the belt was wound around the driven pulley with a smaller diameter by the action of a force countering the pressing force of the spring to widen the gap between the grooves of the driven pulley, thereby increasing the speed. Regarding the speed change responsiveness, when the rotation speed of the driven pulley exceeded 2000 rpm when the rotation speed of the driving pulley was 4000 rpm, the belt was evaluated as A (excellent), and when it was 2000 rpm or less, the belt was evaluated as B (poor).

[0060] <Durability> 4 shows a belt running tester 40 for evaluating durability. This belt running tester 40 for evaluating durability includes a drive pulley 41 having a pulley diameter of 200 mm, and a driven pulley 42 having a pulley diameter of 140 mm provided beside the drive pulley 41.

[0061] The double cogged V-belt B of each of Examples 1 to 6 and Comparative Examples 1 to 4 was wound between a driving pulley 41 and a driven pulley 42, and an axial load DW (dead weight) of 1800 N was applied to the driven pulley 42 to generate belt tension, and the driving pulley 41 was rotated at 4800 rpm under a rotational load of 30 N m to run the belt. The running time until the double cogged V-belt B was broken was then measured. The durability was expressed as a relative value when the running time of Comparative Example 1 was taken as 100.

[0062] (Test Results) The test results are shown in Table 2. According to Table 2, E' L is 220MPa or less and E' H It can be seen that in Examples 1 to 6, where E' is 220 MPa or more, the gear shift response is excellent and the transmission capacity is high compared to the standard Comparative Example 1. L Although E' is 220MPa or less, H In Comparative Example 2, where the E' is 220 MPa or less, the gear shift response is excellent, but the transmission capacity is only at the same level as that of the standard Comparative Example 1. H Although E' is 220 MPa or more, L It can be seen that in Comparative Examples 3 and 4, where the transmission pressure is 220 MPa or more, the transmission capacity is high but the gear shift response is poor.

[0063] [Table 2] [Industrial Applicability]

[0064] The present invention is useful in the technical field of power transmission belts. [Explanation of symbols]

[0065] B Double-cogged V-belt (power transmission belt) 11 Belt body 11a V side 111 Compressed rubber layer 111a Lower cog forming part 112 Adhesive rubber layer 113 Tension rubber layer 12 Covering cloth 13 Lower cog 14 Core Wire 15 Upper cog 20 Test Pieces 30,40 Belt running test machine 31,41 Drive pulley 32,42 Driven pulley

Claims

1. A power transmission belt in which a power transmission portion on a V-side surface is formed of a rubber composition, The rubber composition has a compression vertical elastic modulus E' when a load vibration of a compressive stress between 0.25 MPa and 0.5 MPa is applied at a temperature of 100° C. in the belt width direction at a frequency of 10 Hz. L The storage elastic modulus E' of compression when a load vibration of a compressive stress between 1.0 MPa and 2.0 MPa is applied at a frequency of 10 Hz at a temperature of 100°C is 214 MPa or less. H The power transmission belt has a compressive strength of 231 MPa or more.

2. The power transmission belt according to claim 1, The compression storage modulus E' H The compression storage modulus E' L The ratio of the power transmission belt to the total weight of the belt is 1.1 or more and 1.28 or less.

3. The power transmission belt according to claim 1 or 2, The rubber composition of the power transmission belt contains a rubber component.

4. The power transmission belt according to claim 3, The rubber component of the power transmission belt comprises chloroprene rubber.

5. The power transmission belt according to claim 3 or 4, The rubber composition of the power transmission belt contains cellulose-based fine fibers.

6. The power transmission belt according to claim 5, The power transmission belt, wherein the content of the cellulose-based fine fibers in the rubber composition is 1 part by mass or more and 10 parts by mass or less per 100 parts by mass of the rubber component.

7. The power transmission belt according to any one of claims 3 to 6, The rubber composition of the power transmission belt contains short fibers.

8. The power transmission belt according to claim 7, The rubber composition has a content of the short fibers of 20 parts by mass or more and 40 parts by mass or less per 100 parts by mass of the rubber component.

9. The power transmission belt according to claim 7 or 8, The power transmission belt, wherein the staple fibers include para-aramid staple fibers.

10. The power transmission belt according to claim 9, A power transmission belt comprising copolyparaphenylene-3,4'-oxydiphenylene terephthalamide staple fibers, the staple fibers being para-aramid staple fibers.

11. The power transmission belt according to any one of claims 3 to 10, The rubber composition contains cellulose-based fine fibers and short fibers, The power transmission belt has a rubber composition having a content of the short fibers greater than a content of the cellulosic fine fibers.

12. The power transmission belt according to claim 11, a mass ratio of a content of the short fibers to a content of the cellulose-based fine fibers in the rubber composition is 7 or more and 17 or less.

13. The power transmission belt according to any one of claims 3 to 12, The rubber composition of the power transmission belt contains carbon black.

14. The power transmission belt according to claim 13, The rubber composition has a carbon black content of 30 parts by mass or more and 70 parts by mass or less per 100 parts by mass of the rubber component.

15. The power transmission belt according to any one of claims 3 to 14, The rubber composition contains cellulose-based fine fibers and carbon black, The power transmission belt has a rubber composition having a carbon black content greater than a cellulosic fine fiber content.

16. The power transmission belt according to claim 15, a mass ratio of a content of the carbon black to a content of the cellulose-based fine fibers in the rubber composition is 10 or more and 30 or less.

17. 17. The power transmission belt according to claim 3, The rubber composition contains carbon black and short fibers, The power transmission belt, wherein the content of the short fibers in the rubber composition is less than the content of the carbon black.

18. The power transmission belt according to claim 17, A power transmission belt, wherein a mass ratio of a content of the short fibers to a content of the carbon black in the rubber composition is 0.35 or more and 0.75 or less.

Citation Information

Patent Citations

  • Knocking detecting device for internal combustion engine

    JP1987071823A

  • Transmission belt

    JP2016211589A

  • V-belt and production method therefor

    WO2015045255A1